LOCAL JUSTICE WITHOUT RECOGNITION: THE CRISIS OF LEGITIMACY OF MARIND CUSTOMARY JUSTICE - Mulyadi Alrianto Tajuddin; Marlyn Jane Alputila (LPPM STIH Putri Maharaja, 2026)
Papua customary justice is a vital expression of Indonesia’s legal pluralism, serving as a community-based dispute-resolution mechanism grounded in restorative and collective values. This study examines the contemporary dynamics of the Marind customary court in South Papua and explores strategies to strengthen it amid legal modernization. Using an empirical juridical approach supported by document analysis and field observations, the research analyzes the interaction between customary norms and state law. The findings show that the Marind customary court remains socially legitimate and functionally relevant. Yet, its existence is constrained by normative tensions with national criminal law and formal land governance, resulting in legal uncertainty and the marginalization of customary authority. The dominance of oral tradition further increases institutional vulnerability in the context of generational change. To address these challenges, the study proposes integrated strategies, including participatory documentation of customary law, capacity building for customary authorities, and legislative harmonization, to secure formal recognition while preserving indigenous legal values.